#TITLE_ALTERNATIVE# - SANDRO FERDIAN MANURUNG (NIM:15011140), MARTUA
Earthquake is a shaking phenomenon that occurs in the earth’s surface due to the release of energy from the earth suddenly that creates seismic waves. The earthquake generated a lot of impact on the earth, one of which is damage to infrasturcture. Indonesia is a country that has a high level of seismic vulnerability because it lies on the track of The Pacific Ring of Fire and was among the biggest three tectonic plates in the world namely India plate, the Australian plate and the Pacific plate. Risk analysis (risk assessment analysis) performed on the housing infrastructures consisted of Infill Frame (INF) and Confined Masonry (CM) building types. By using the map of RDTR (Zonation Code) DKI Jakarta, can be identified the area of residential with those building types. Vulnerability of buildings to a spectral acceleration represented in a fragility curve. By doing a join data of peak ground acceleration (PGA) with the fragility curve can be obtained the magnitude of the probability if collapse of the building at each level of damage. A final criteria of the earthquake risk is obtained by calculating the probability of collapse at the level of ‘damaged’ and ‘collapse’ and join them with the value of Building Base Coefficient (KDB) in a zone. The results of the risk analysis based on the earthquake scenarios visualized in the risk maps in each district in Jakarta.